Pemanfaatan Layanan SMS Telepon Seluler Berbasis Mikrokontroler Atmega328p Sebagai Sistem Kontrol Lampu Rumah - Endri Maulana; Rachmat Adi Purnama (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Lighting conditions of a house abandoned by the owner of a business for a long time to get home tonight. This makes the owner let the condition of the house in the dark at night when the weather starts. Therefore, to overcome it needed an integrated system with various devices in the home. This system also needs to be controlled by the homeowner from a distance. An SMS (Short Message Service) can be a solution, because almost every homeowner has a cell phone that supports SMS. Home lighting system is controlled by a microcontroller Atmega 328P as a control center connected to the device to turn on the house lights. Besides the microcontroller is connected with wavecome modem that serves as a device that receives short messages to be sent by the owner of the house.Key Words: SMS, Mikrokontroler Atmega328P, Modem Wavecome